1895 Cal. Stat. 63-64 - (:unkn) unknown (My University, 1895)
Amendments to the Civil Code, Chapter 168-An Act to Amend Several Sections Relating to the National Guard of California, § 1942: Prohibited militias to wear colors not associated with the United States. Prohibited any unorganized militia other than the regular organized National Guard in the state of California without a license from the governor. Violators guilty of a misdemeanor subject to arrest and punishment therefor.
Keywords: MILITIAS